2004
DOI: 10.1148/radiol.2312021708
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Disk Herniation: Correlation of Histologic Findings with Marrow Signal Intensity Changes in Vertebral Endplates at MR Imaging

Abstract: Avulsion-type disk herniation seems to be common, and vertebral endplate marrow signal intensity changes on MR images are indicative of cartilaginous material in the extruded disk herniation material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
85
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(92 citation statements)
references
References 28 publications
1
85
0
5
Order By: Relevance
“…Elderly people (over 60 years old) were excluded because of the common, age-dependent, degenerative changes in intervertebral discs and bone marrow, which may hamper the assessment of the subchondral abnormalities. The number of patients in this study was limited because M1 as a single finding is not common among patients with chronic LBP even though it is in association with disc herniation [2,22]. In our study, the carefully selected group of LBP patients with M1 consisted of 24 (2.4%) patients of the 1,015 base population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Elderly people (over 60 years old) were excluded because of the common, age-dependent, degenerative changes in intervertebral discs and bone marrow, which may hamper the assessment of the subchondral abnormalities. The number of patients in this study was limited because M1 as a single finding is not common among patients with chronic LBP even though it is in association with disc herniation [2,22]. In our study, the carefully selected group of LBP patients with M1 consisted of 24 (2.4%) patients of the 1,015 base population.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the carefully selected group of LBP patients with M1 consisted of 24 (2.4%) patients of the 1,015 base population. In previous studies, the reported prevalence of subchondral signal abnormalities varies, that of hypointensities between 4% and 16% [2,6,11,13,17,22]. This is obviously due to varying criteria for abnormalities and selection of subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modic-associated proinflammatory biochemical mediators have been suggested to be a major origin of pain [6]. MT1 converts to either MT2 or to a normal stage from 14 months to 3 years [20].…”
Section: Discussionmentioning
confidence: 99%
“…This is accompanied by increased vascular density, increased number of nerve endings and increased levels of proinflammatory biochemical mediators [5], which might be of pathogenic importance for the development of pain [6]. Generally, Modic type 2 (MT2) and type 3 changes are thought to represent the end stage of the degenerative process, and are not assumed to cause symptoms [7].…”
mentioning
confidence: 99%